Kualitas Pelayanan Program Jaminan Kesehatan Nasional (JKN) di RSUD Muntilan Kabupaten Magelang - Retma Balqis Bestari; Puji Astuti; Nunik Retno H (Journal of Politic and Government Studies, 2014)
ABSTRACTOne of the Government steps to fulfill the society needs in health sector is by making JKN program. RSUD Muntilan is Magelang Regency hospital that’s classified to be type C hospital which has facilities in medical specialist ability and becomes reference hospital in Magelang Regency and surounding. RSUD Muntilan always tries to give best service for all patients. But, in fact there are complaints from the patients who’s in JKN Program. Those complaints such as service procedures that aren’t flexible and slow respons due to patients needs.This research is done to know the service quality of JKN Program thats given to the in house patients class III in RSUD Muntilan. The indicator for service quality of JKN are reliability, responsiveness, assurance, emphaty, and tangible. This research is descriptive research with quantitative analytical to describe the service quality of JKN. The tecnic used for collecting data used quesioner given to the patients. Data proceed using Importance and Performance Analysis (IPA) which is patients expectation measurement thats linked to hospital service capability. This will be value of IPA used to count the value of analysis satisfaction index (CSI). So we can get the value of patients satisfaction level due to the service quality.The result show the service quality of JKN program that given by RSUD Muntilan Magelang regency is well done. We can know it from the CSI result that show the satisfaction level up to 83,80 %. The indicator with the highest hope level according to the patients is reliability (4,81%) while the indicator lowest hope level is tangible (4,47 %). But in assesment show that reliability has the lowest point among others (4,15). Patients themeselves haven’t gutten satisfied enough with the service especially the fast and exact service and direct service procedure. Based on the compapibility between expectation and the reliability it becomes the major priority in sevice quality improvement.2Key words : Service Quality, National Health Assurance Program (JKN),Reliability, Responsiveness, Assurance, Emphaty, Tangible